2019
DOI: 10.1177/0956797619844269
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Hold Mixed Emotions About Racial Out-Groups? A Case for Affect Matching

Abstract: Increased contact between members of different racial groups is often conceptualized as an antidote to racism (Pettigrew & Tropp, 2006). Some studies, however, find that people living in racially diverse areas report higher levels of racism than those living in homogenous enclaves (Putnam, 2007). Further, increased immigration and racial diversity within nations has been associated with a number of divisive geopolitical trends, such as the British exit from the European Union and the rise of White nationalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 43 publications
6
40
0
Order By: Relevance
“…Árnadóttir, Lolliot, Brown, & Hewstone, 2018). These differences may emerge because negative and positive contact impact different variables to different extents (Aberson, 2015;Barlow et al, 2019). In our longitudinal study, we found evidence consistent with an effect of positive contact on intercultural competence, but no evidence of an effect of negative contact on this outcome.…”
Section: Discussionmentioning
confidence: 43%
“…Árnadóttir, Lolliot, Brown, & Hewstone, 2018). These differences may emerge because negative and positive contact impact different variables to different extents (Aberson, 2015;Barlow et al, 2019). In our longitudinal study, we found evidence consistent with an effect of positive contact on intercultural competence, but no evidence of an effect of negative contact on this outcome.…”
Section: Discussionmentioning
confidence: 43%
“…Multiple other mechanisms explaining specifically primary (but not secondary) transfer effects of positive contact have been identified. These comprise affective variables such as different intergroup emotions (e.g., anger: Barlow et al, 2019;disgust and admiration: Cernat, 2011;fear: Kauff et al, 2017;Seger et al, 2017) and numerous cognitive processes (e.g., knowledge about the outgroup: Brown & Hewstone, 2005); social norms (perceptions of how ingroup members think and act: Christ et al, 2014;Paterson et al, 2019;Turner et al, 2008;Wang et al, 2019); inclusion of the other in the self (perceived closeness between the self and outgroup: Page-Gould et al, 2010;Turner et al, 2008); self-disclosure (disclosure of personal information about self to other: Frølund Thomsen, 2012;Turner, et al, 2007); dehumanization or infrahumanization (denying elements of humanness to outgroups: Prati & Loughnan, 2018;Stathi et al, 2017); perceived importance of and satisfaction with contact (Frias-Navarro et al 2020;van Dick et al, 2004); perceived outgroup heterogeneity (perception of similarity between outgroup members: Čehajić et al, 2008); stereotypes of outgroup warmth and competence (Kotzur et al, 2019;Zingora et al, 2020); and metastereotypes (beliefs about the stereotypes that outgroup members hold about their group: Mazziotta et al, 2011). It is plausible to expect many of these processes (e.g., emotions, social norms, outgroup evaluations) to generalize from primary to secondary outgroups and thus underlie not only the primary but also secondary transfer effects.…”
Section: Mediators Of Specifically Primary Transfer Effectsmentioning
confidence: 99%
“…They found that positive information about outgroup members had a greater impact on evaluations of positively stereotyped outgroups, whereas negative contact had a greater impact on the evaluations of negatively stereotyped outgroups. Additional explanations for the mixed findings focused on specific outcome variables: Based on results from a large data set from New Zealand, Barlow et al (2019) suggest that positive contact might have a greater effect on positive emotions (i.e., warmth), whereas negative contact has a stronger effect on negative emotions (i.e., anger). Aberson 2015, on the other hand, examined whether positive and negative contact would differentially influence affective and cognitive factors.…”
Section: The Emerging Field Of Research On Positive and Negative Contactmentioning
confidence: 99%